Characterization of Permeability Changes in Coal of High Rank during the CH4-CO2 Replacement Process - X. M. Ni; Q. F. Jia; Y. B. Wang (Geofluids)
The influences of coal matrix expansion/contraction and effective stress on the permeability of coal with different thermal maturities are different during the CH4-CO2 replacement process due to different mechanical properties and gas adsorption capacities. To accurately predict the variation law of coal permeability during the CH4-CO2 replacement process, it is critical to understand how the matrix expansion/contraction and effective stress affect the permeability of coal at different thermal maturities during the CH4-CO2 replacement. In this study, the permeability of two coal specimens with anthracite and high-rank bituminous coal during the CH4-CO2 replacement process under different confining and injection pressures was tested using a CBM replacement testing machine. The results demonstrate that with decreasing gas injection pressure, the permeability of the two coal specimens exhibited a U-shaped correlation under different confining pressures. Under the same gas injection pressure, with increasing effective stress, the permeability presented a negative exponential decrease and the permeability of the anthracite decreased more significantly. Moreover, under the same confining pressure, with increasing gas injection pressure, the decreasing permeability agreed with Langmuir curve and the permeability of high-rank bituminous coal was more significantly reduced.